Economic efficiency of personalized rehabilitation programs for knee joint injuries conducted under ultrasound monitoring - Khamidov Obid Abdurahmanovich; Dadamyants Natalia Gamletovna; Umarova Nargiza Nuritdinovna; Usarov Mukhriddin Shukhratovich (THE INNOVATION ECONOMY, 2026)
Treatment and rehabilitation after knee joint injuries are associated with significant economic costs, including direct medical expenses and indirect losses due to temporary disability. Standardized rehabilitation protocols do not always account for individual recovery rates, which can lead to prolonged treatment periods and increased risk of complications. To conduct a comprehensive clinical and economic analysis and evaluate the cost effectiveness of individualized rehabilitation programs for patients with post-traumatic knee joint complications, performed under dynamic ultrasound (US) monitoring, compared to the standard management protocol.